(untitled) (Journal of Pathology of Nepal, 2021)
Struma ovarii, also known as goiter of the ovary is a rare disease.1 Considering the rarity of this tumor and constrained literature in Nepal’s context, we hereby present a case of a 46-year-old female, asymptomatic, with normal blood parameters who presented with an abdominal mass. She was suspected of malignant ovarian mass on an ultrasonogram. Intraoperative frozen section examination revealed a benign tumor suggestive of dermal tumor versus struma ovarii. Postoperatively, histopathological examination was performed to assess the percentage of thyroid tissue and a diagnosis of benign struma ovarii was made which was confirmed by thyroglobulin positivity on immunohistochemistry. No features of immature teratoma and malignancy were identified.